1994
DOI: 10.1073/pnas.91.10.4569
|View full text |Cite
|
Sign up to set email alerts
|

The modulatory action of loreclezole at the gamma-aminobutyric acid type A receptor is determined by a single amino acid in the beta 2 and beta 3 subunit.

Abstract: Type A yaminobutyric acid (GABAA) receptors of the mammalian nervous system are a family of ligandgated ion channels probably formed from the coassembly of different subunits (a1.6, Pl39 8) in the arrangement apy or ad8. The activation of these receptors by GABA can be modulated by a range ofcompounds acting at distinct allosteric sites. One such compound is the broad-spectrum anticonvulsant loreclezole, which we have recently shown to act via a specific modulatory site on the P subunit of the GABAA receptor. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
129
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(135 citation statements)
references
References 29 publications
(22 reference statements)
6
129
0
Order By: Relevance
“…The selectivity of etomidate (as well as loreclezole) is dependent on an asparagine residue at position 265 of the GABA A receptor β2 subunit (Wingrove et al, 1994). The results from our sleep time study, together with the results from the motor activity analysis, lend credence the notion that a decrease in β2 protein expression translates to a functional loss of the GABA A receptor activity.…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micesupporting
confidence: 69%
“…The selectivity of etomidate (as well as loreclezole) is dependent on an asparagine residue at position 265 of the GABA A receptor β2 subunit (Wingrove et al, 1994). The results from our sleep time study, together with the results from the motor activity analysis, lend credence the notion that a decrease in β2 protein expression translates to a functional loss of the GABA A receptor activity.…”
Section: Behavioural Phenotype Of Fmr1 Knockout Micesupporting
confidence: 69%
“…The results obtained with the chimeric ␤ 1-2 and ␤ 2-1 subunits demonstrate that structural elements that reside within the transmembrane domains, connecting loops, or carboxylterminal region of the ␤ subunit are important for both the GABA-modulatory and GABA-mimetic effects of etomidate. The GABA-modulatory effects of loreclezole exhibit a similar profile (18). For this anticonvulsant, site-directed mutagenesis studies have highlighted the importance of an asparagine residue (␤ 2 and ␤ 3 ) versus a serine residue (␤ 1 ) located toward the carboxyl-terminal end of the second transmembrane domain, the putative pore-forming region of the chloride ion channel (18).…”
Section: Discussionmentioning
confidence: 99%
“…of the ␤ subunit (an asparagine for ␤ 2 and ␤ 3 and a serine for ␤ 1 ) dictates the differential interaction of this anticonvulsant with the GABA A receptor (18). Similarly, for oocytes expressing ␣ 6 , ␥ 2L and a ␤ 1 subunit in which this serine was changed to an asparagine residue (␤ 1 S290N ), both the potency (EC 50 ϭ 1.6 Ϯ 0.3 M) and the maximal effect (E max ϭ 150 Ϯ 13%, n ϭ 5) of etomidate was increased relative to receptors (␣ 6 ␤ 1 ␥ 2L ) expressing the wild-type ␤ 1 subunit (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wingrove et al (1994) who expressed the b1/2 chimeras and some of the point mutations with a1 and g2s reported that the affinities for GABA were unchanged. In this study, the EC 20 values of most of the chimeras and point mutations were not significantly different from the wild-type receptors (the exceptions being a2b1g2s vs a2b2 1-237 b1 238-474 g2s and a2b1g2s vs a2b2N289Sg2s one-way ANOVA with Tukey Kramer post hoc test).…”
Section: T255 and I308 Of The B1 Subunit Are Required For Inhibition mentioning
confidence: 99%